Pembuatan Indeks Beranotasi Artikel Surat Kabar Padang Ekspress tentang Subjek Pendidikan Koleksi Dinas Kearsipan dan Perpustakaan Provinsi Sumatera Barat - Rafiulillah, Susan; Nurizzati, Nurizzati (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2017)
The writing of this article aims to identify the existence of newspapper and deacribe the process of making annotated index of articlea Padang Express's Newspapper from January to May 2016 on the subject education Archives and Library of West Sumatera. Data done by study document, collect data directly from the original source, that is Archieves and Library of West Sumatera.Based on the result in the index making annotated article newspaper there are several steps muat be considered are : (1) early observation of the newspaper to be index (2) article's newapaper selection, the articles are from Padang Express newspaper from January to May 2016; (3)make a description of newspaper articles, articlea tittle, author's name, newspaper tittle which contained article, days, date and year of the article and article's pages in the newspaper; (4) making annotation of the newspaper, the point of information that contained in newspaper; (5) making keyword; the words that often appear and easily understood by public in the article information. (6) making article's newspaper index start from writing author's name and writing of the newspaper's article title (7) compile the annotated index of newspaper articles; and (8) typing index.Keywords: Index, Annotated,Â Article, Newspapers